OC-87 Gaucher disease in romania – baseline characteristics, specific diagnosis. treatment and outcome. (6th June 2017) - Bucerzan, Simona; AlKhzouz, Camelia; Nascu, Ioana; Zimmerman, Anca; Popp, Radu; Lazea, Cecilia; Grigorescu-Sido, Paula
Abstract : Gaucher disease is a autosomal recessive inherited monogenic disease caused by beta-glucocerebrosidase deficiency. Clinically, there are three types: type 1 (non-neuronopathic), type 2 (acute neuronopathic) and type 3 (chronic neuronopathic), in 92%, 1% and respectively 7% of patients. Specific diagnosis has been possible in Romania since 1997 and enzyme replacement therapy since 2002. The aim of the study is to present the epidemiologic, clinical and molecular data of the Romanian patients with Gaucher disease ant their evolution. Patients and methods: Seventy-nine patients (76 patients with Gaucher disease type 1 and 3 patients with Gaucher disease type 3; F/M=1.37/1) were evaluated clinically and by measurement of haemoglobin, thrombocytes, hepatic and splenic volume, chitotriosidase, bone density (Z score) and severity index at diagnosis and every each 6–12 months. Sixty-nine patients were treated with imiglucerase for a period of 1–13 years. Results: Gaucher disease prevalence in our country, evaluated according to the number of patients diagnosed, is 1/250, 000 vs. the potential prevalence of 1/100, 000. Mean age at clinical onset was 15.4 years and 28.8 years at specific diagnosis. We found a high incidence of genotype N370S/L444P (38%) and of genotype N370S/? (32%), predictive for a severe phenotype vs 15.3% and 9.6% respectively in patients reported in International Gaucher Registry. Splenectomy was effectuated in 30% patients before the enzyme replacement therapy. Anaemia, thrombocytopenia, splenomegaly and bone disease was present in 52%, 37.7%, 100% and 91% of patients. The status of untreated patients was progressively worsening and four of the patients died. Enzyme replacement therapy led to normalisation of haemoglobin, thrombocytes, hepatic volume and chitotriosidase after 0.5, 1.5, 2 and 3 years respectively. After 4 years of treatment, splenomegaly has been reduced from 14.4 of normal to 3.06 of normal. Clinical evolution of bone disease was favourable. Conclusion: Gaucher disease is still undiagnosed in our country. Severe forms of disease are more prevalent. The patients have access to specific, enzyme and molecular diagnosis. Evolution under enzyme replacement therapy is very good.